Láng Nándor, az első bölcsész rektor élete és munkássága - Gesztelyi, Tamás (Gerundium, 2011)
The Life and Work of Nándor Láng, the First Philologist Rector. Nándor Láng, who came from a German family, in the service of the shared goals of a multicultural Hungary prioritized those ideals which asserted the education of an increasing number of  sophisticated scholars and scientists as well as elevating domestic science and scholarship to an international level. In the first period of his career, as a secondary-school teacher, he focussed on supporting the promulgation and teaching of classical culturethrough his scholarly activity, including the authoring of textbooks. A crucial turning-point in his life occurred when he was invited in 1914 to serve as head of one (Latin) of the departments of Classical Philology of the newly created University of Debrecen. In the academic year of 1916/1917 he was Rector of the university, a service that he fulfilled with a maximum commitment and a truly professional approach. The combination of his professional erudition and human characteristics made him an ideal pedagogue.He was active in Debrecen until 1932, when he retired, but he continued to carry on significant sholarly activity in the archeology and epigraphy of the Roman period in Pannonia.